Life‐threatening necrotizing myometritis, due to Group A streptococcus – still a life‐threatening condition. Issue 5 (13th February 2015) - Boie, Sidsel; Krog, Jan; Tørring, Sofus; Bor, Isil Pinar
Key Clinical Message Puerperal infection with Group A streptococcus (GAS) can present with few symptoms and rapidly progress to a life‐threatening condition. Often, the infection can be treated with antibiotics. Delay in diagnosis increases risk of sepsis, multiorgan failure, and death. GAS infection is a differential diagnose for all postpartum women with unexplained symptoms.